Health Counseling About Rheatoid Arthritis In RT 26 Sawah Lebar District, Bengkulu City - Maharani, Nanda; Putri Alessandra, Azelya; Windiah, Nola; Purnamasari, Fita; Lestari, Puja; Marliza, Marliza; Surahman, Fery (Jurnal Pengabdian Mandiri, 2024)
Based on data from the World Health Organization (WHO) in 2016, approximately 335 million people worldwide suffer from rheumatism. According to data from the Health Office of Bengkulu City in 2019, based on doctor diagnoses, the prevalence is 11.11%. Gout arthritis is among the top 10 most prevalent diseases in Bengkulu City, ranking 7th (Health Office of Bengkulu City, 2020).The aim of this study is to assess the frequency distribution of knowledge before and after conducting educational activities on rheumatoid arthritis, focusing on improving public understanding as a preventive measure against the disease. The method used in this research involved two activities: lectures and Q&A sessions. Results and Discussion: In this community service activity titled "Health Education on Rheumatoid Arthritis in Rt. 26, Sawah Lebar Subdistrict, Bengkulu City," analysis of questionnaire responses showed a significant increase in knowledge distribution between the pre-test and post-test phases. Initially, the average knowledge score was 65 (fair), which improved to 80 (good) after the education session. This indicates the effectiveness of the intervention in enhancing elderly understanding of rheumatoid arthritis. Recommendations: The results of this rheumatoid arthritis education activity are expected to provide information that enhances public understanding of the importance of prevention and management of rheumatoid arthritis. Based on data from the World Health Organization (WHO) in 2016, approximately 335 million people worldwide suffer from rheumatism. According to data from the Health Office of Bengkulu City in 2019, based on doctor diagnoses, the prevalence is 11.11%. Gout arthritis is among the top 10 most prevalent diseases in Bengkulu City, ranking 7th (Health Office of Bengkulu City, 2020).The aim of this study is to assess the frequency distribution of knowledge before and after conducting educational activities on rheumatoid arthritis, focusing on improving public understanding as a preventive measure against the disease. The method used in this research involved two activities: lectures and Q&A sessions. Results and Discussion: In this community service activity titled "Health Education on Rheumatoid Arthritis in Rt. 26, Sawah Lebar Subdistrict, Bengkulu City," analysis of questionnaire responses showed a significant increase in knowledge distribution between the pre-test and post-test phases. Initially, the average knowledge score was 65 (fair), which improved to 80 (good) after the education session. This indicates the effectiveness of the intervention in enhancing elderly understanding of rheumatoid arthritis. Recommendations: The results of this rheumatoid arthritis education activity are expected to provide information that enhances public understanding of the importance of prevention and management of rheumatoid arthritis.